Urban pollution greatly enhances formation of natural aerosols over the Amazon rainforest - Manish Shrivastava (Nature Portfolio, 2019)
It remains unclear how urban emissions influence the formation of secondary organic aerosols (SOA), including in the Amazon forest. Here, the authors simulate the formation of SOAs in the Amazon using a high-resolution regional chemical transport model. They find that urban emissions of NOx from Manaus enhance the production of biogenic SOA by 60–200%.